Effects of environmental exposure on tribological properties of Arhar particulate/epoxy composites. Issue 9 (15th February 2017) - Om Prakash, M.; Raghavendra, G.; Panchal, Manoj; Ojha, S.; Anji Reddy, Bhavanam
Abstract : The solid particle erosion behavior of Arhar particulate epoxy composites with 5, 10, and 15 wt% particulate content has been characterized. The Arhar particulate epoxy composites have been fabricated using hand lay‐up technique, and samples have been exposed to different environmental conditions, such as dry, saline, mineral water, kerosene, and subzero, before erosion test. The effect of different environments on erosion wear rate is investigated for all the composites. The rate of erosion at which Arhar particulate epoxy composites undergo when subjected to various impingement angles (30, 45, 60, and 90°) and at particle speeds ( v  = 86, 101, and 119 m/s) using air jet erosion test rig has been evaluated. Erosion behavior of Arhar particulate composites is found to be less when compared with neat epoxy material. Normal samples showed semibrittle erosive behavior. Erosive wear rate is more in samples with 15 wt% particulate content. Erosion wear is higher in samples immersed in saline water. Erosive wear behavior samples immersed in saline water, mineral water, and kerosene, which is found to be semibrittle. POLYM. COMPOS., 39:3102–3109, 2018. © 2017 Society of Plastics Engineers